2016
DOI: 10.1016/j.actamat.2016.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale characterization and modeling of 60° dislocations in a high-entropy alloy

Abstract: High-entropy alloys (HEAs) are an exciting new class of multi-component alloys some of which haveunusual and remarkable properties. As of yet, little is understood about dislocation core structure and stacking fault energies in these alloys. For this study, a five-component, equiatomicalloy (CrMnFeCoNi) was deformed to 5% plastic strain at room temperature. Posttest observations using diffraction contrast scanning transmission electron microscopy (DC-STEM) analysis provide evidence for numerous planar slip ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(88 citation statements)
references
References 42 publications
7
81
0
Order By: Relevance
“…The line tension parameter α = 0.123 is obtained from the atomistically-measured edge dislocation line tension in the EAM FeNiCr effective matrix, and is close to the coefficient for elemental Al [82]. The dislocation cores in HEAs show large dissociation distances d > 10b, consistent their relatively low stacking fault energies γ SF (low ab initio estimates, and large stacking fault ribbons observed experimentally [100,101,102]). The minimized parameters of Eqs.…”
Section: Fcc High Entropy Alloysmentioning
confidence: 99%
“…The line tension parameter α = 0.123 is obtained from the atomistically-measured edge dislocation line tension in the EAM FeNiCr effective matrix, and is close to the coefficient for elemental Al [82]. The dislocation cores in HEAs show large dissociation distances d > 10b, consistent their relatively low stacking fault energies γ SF (low ab initio estimates, and large stacking fault ribbons observed experimentally [100,101,102]). The minimized parameters of Eqs.…”
Section: Fcc High Entropy Alloysmentioning
confidence: 99%
“…Therefore, it seems that the low SFE of CoCrFeMnNi HEA is a deterministic factor in the evolution of the defect structure during HPT. It is noted that a recently published study [33] showed that in a CoCrFeMnNi HEA the value of SFE may have a spatial dependence due to the variation of local chemical composition. This effect yields a different degree of dislocation dissociation into partials.…”
Section: Evolution Of Lattice Defect Structure In Cocrfemnni Hea Durimentioning
confidence: 99%
“…The MD calculations are used for predicting the thermomechanical properties, which computes the materials from a molecular-scale and has a very extensive range of applications [137]. MD is well suited to reproduce the smart amplitude oscillations of atoms in the vicinity of crystal-lattice sites.…”
Section: Calculationsmentioning
confidence: 99%